2012
DOI: 10.5511/plantbiotechnology.12.0530a
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from embryogenic tissue of Pinus luchuensis Mayr, an endemic species in Ryukyu Island, Japan

Abstract: Somatic embryogenesis in Ryukyumatsu (Pinus luchuensis Mayr.), an endemic species in Ryukyu Island, Japan, was initiated from megagametophytes containing zygotic embryos on a medium supplemented with 10 µM 2,4-dichlorophenoxyacetic acid and 5 µM 6-benzylaminopurine. Embryogenic cultures were maintained and proliferated by subcultures at 2-to 3-week-intervals on the same fresh medium. e maturation of somatic embryos occurred on media containing maltose, activated charcoal, abscisic acid and polyethylene glycol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…ET induction of JPs was initiated from whole megagametophytes containing immature zygotic embryos (Maruyama et al, 2005a,b, 2007; Hosoi and Maruyama, 2012). Seeds were disinfected with 1–2% sodium hypochlorite solution for 15–20 min (Maruyama and Hosoi, 2014).…”
Section: Induction and Proliferation Of Etmentioning
confidence: 99%
See 2 more Smart Citations
“…ET induction of JPs was initiated from whole megagametophytes containing immature zygotic embryos (Maruyama et al, 2005a,b, 2007; Hosoi and Maruyama, 2012). Seeds were disinfected with 1–2% sodium hypochlorite solution for 15–20 min (Maruyama and Hosoi, 2014).…”
Section: Induction and Proliferation Of Etmentioning
confidence: 99%
“…In general, the extrusion of ET occurred 2–6 weeks after culture, and the proliferation of ET became obvious after 4–8 weeks of culture when EM increased (Maruyama and Hosoi, 2014). The induction frequency on the medium supplemented with PGRs varied from 1.0 to 2.8%, with an overall average of 2.3% (Maruyama et al, 2005a,b, 2007; Hosoi and Maruyama, 2012), which was comparable with previous results for P. densiflora (up to 2.3%, Kim and Moon, 2014), P. nigra (3.1%, Salajová and Salaj, 2005), Pinus banksiana (up to 3.9%, Park et al, 2006), P. rigida × P. taeda (up to 1.1%, Kim and Moon, 2007b), and P. lambertiana (1–3%, Gupta, 1995). These results were inconsistent with the high induction rates reported for P. radiata (44–93%, Hargreaves et al, 2011), P. taeda (up to 79%, Gupta, 2014), P. strobus (54%, Finer et al, 1989), Pinus sylvestris (up to 30%, Aronen et al, 2009), and P. pinaster (up to 75%, Park et al, 2006).…”
Section: Induction and Proliferation Of Etmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to studies of somatic embryo maturation of Picea abies , in which PEG is reported to stimulate embryogenesis but inhibit the subsequent germination process [ 72 ]. Partial desiccation and/or cold treatments after maturation on medium containing PEG have been reported necessary to improve somatic embryo germination and conversion in a number of conifer species, including some pines [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ], spruces [ 80 , 81 , 82 , 83 ], hybrid larch [ 84 ], Fraser fir [ 66 ], and Chinese fir [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…The positive effect of PEG on embryo maturation has been reported for many coniferous species, including Picea abies (Hudec et al, 2016), P. likiangensis (Chen et al, 2010), P. glauca (Stasolla et al, 2002;Stasolla & Yeung, 2003), and Cryptomeria japonica (Maruyama et al, 2007). Hosoi and Maruyama (2012) reported a 25-fold increase in the number of mature embryos produced in Pinus luchuensis, relative to the number of mature embryos produced in PEG-free medium when embryogenic tissue was incubated on a medium containing 15% PEG. Tret'yakova and Barsukova (2012) reported that somatic embryos of Larix sukaczewii only developed and matured on a medium supplemented with 10% PEG.…”
Section: Introductionmentioning
confidence: 99%